Nilai-nilai Pendidikan Toleransi dalam Kegiatan Bahs Al-Masāil di Pesantren Tradisional - Habib Maulana Maslahul Adi (Asatiza: Jurnal Pendidikan, 2022)
This study aims to reveal the educational value of tolerance contained in bahs al-masāil activities in traditional Islamic boarding schools. This research is a qualitative descriptive study which took place at the Pesantren Al-Anwar in Rembang and the Pesantren Al-Luqmaniyyah in Yogyakarta, with the object of research being the students from the pesantren who actively participated in the bahs al-masāil forum. Data collection techniques used are interviews and documentation. The results of the study indicate that there are at least four values ​​of tolerance education in bahs al-masāil activities, namely: mutual respect for the opinions of others shown by the bahs al-masāil participants; helping fellow participants in finding 'ta'bīr related to the problem being discussed from the reference book; upholding peace after leaving the baul masāil arena which is full of disputes; and justice realized by the moderator in leading the bahs al-masāil forum